A NATURAL PRODUCT DECURSIN ENHANCES THE RADIOSENSITIZATION OF IONIZING RADIATION AGAINST DMBA-INDUCED TUMOR - SHEHZAD, ADEEB; ZAHID, HIRA; MUHAMMAD, WAZIR; AHMAD, RIZWAN; AL-SUHAIMI, EBTESAM A. (International Journal of Applied Pharmaceutics, 2019)
Objective: Radiation therapy has gained significant attention for the treatment and prevention of solid and malignant human tumors. However, after periodical exposures, radiation therapy losses its efficacy against cancer cells displaying radio-resistant phenotypes. Therefore, decursin might improve the efficiency of radiotherapy against a variety of human cancers. Methods: The chemopreventive efficacy of decursin was evaluated against B16F10 cancer cell lines and DMBA/croton oil-induced skin carcinogenesis in BALB/c mice. Decursin was administered intraperitoneal at the dose of 20 mg/kg/day for 8 weeks following exposure to 5 Gy of ionizing radiation (IR) after 1 month of DMBA application. Western blot was performed for underlying mechanism of radioresistance. Results: Decursin suppressed the proliferation and viability of melanoma cancer cell lines in a concentration- and time-dependent manner. The in vivo data collected from mice model revealed that decursin reduced the precancerous skin lesions and the incidence of tumor bearing in radiation-exposed mice. Decursin also enhanced the effect of IR by downregulation of Akt/NFκB pathway through activation of IκBα. Conclusion: Our results suggest that the activation of Akt/NFκB establishes a pro-survival response to radiation that may account for the development of radioresistance. Decursin blocks the abnormal expression of these proteins and potentiates the radiotherapeutic effect.